An Application of Decision Making Grid to Improve Maintenance Strategies in Small and Medium Industries - M.A., Burhanuddin; A.R., Ahmad; M.I., Desa (IEEE, 2007)
Competitive disadvantages for small and medium industries (SMI), in comparison with the larger ones, essentially result from the restricted personnel possibilities in the administrative and production departments and also the decreasing lot sizes to be fabricated in the productions with reference to a growing product range. Also less number of machines use in the SMI’s, in comparison to the larger ones, which are always grouped together in serial lines. Therefore, it is important to well organize their maintenance structure individually to ensure the effectiveness of the entire production lines. In order to increase the effectiveness of the units, we studied some decision support systems (DSS) to maintain the equipment. Choosing and optimizing maintenance strategies is of formost importance in maintenance management. In this paper, we identified maintenance strategies to the machines based on 2 factors: the downtime and the frequency of machines failures with multiple criterions. We use decision making grid (DMG) model introduced by [1]. Next, maintenance management department can implement these strategies for their machines respectively. The case study is taken from the SMI’s, one of the food processing company in West Malaysia. We have collected a dataset, conduct data analysis and provide few recommendations to the maintenance management.